(untitled) (Journal of Atomic and Molecular Sciences, 2011)
In this paper, the effects of an external field on the early stage decoherence are discussed both in the cavity QED and the spin chain channel. We calculate the evolution of the entanglement, find that the finite time disentanglement can be eliminated or induced by the present of an external field for some initial states.